Protein Folding Prediction in a Cubic Lattice in Hydrophobic-Polar Model - Yanev, Nicola; Traykov, Metodi; Milanov, Peter; Yurukov, Borislav (Journal of computational biology, 2017)
The tertiary structure of the proteins determines their functions. Therefore, the predicting of protein's tertiary structure, based on the primary amino acid sequence from long time, is the most important and challenging subject in biochemistry, molecular biology, and biophysics. One of the most popular protein structure prediction methods, called Hydrophobic-Polar (HP) model, is based on the observation that in polar environment hydrophobic amino acids are in the core of the molecule-in contact between them and more polar amino acids are in contact with the polar environment. In this study, we present a new mixed integer programming formulation, exact algorithm, and two heuristic algorithms to solve the protein folding problem stated as a combinatorial optimization problem in a simple cubic lattice. The results from computational runs on a set of benchmarks are favorably compared to known algorithms for solving the 3D lattice HP model as genetic algorithms, ant colony optimization algorithm, and Monte Carlo algorithm.